Building Bridges Between Criminal Justice and the Forensic Sciences to Create Forensic Studies Programs. - Fradella, HenryF.; Owen, StephenS.; Burke, TodW. (Journal of Criminal Justice Education, 2007)
The ever-increasing role of the forensic sciences in the criminal justice system requires criminal justice educators to integrate the study of forensic science into a traditional social science curriculum. Yet, most professors in criminal justice lack forensic science expertise sufficient to meet the educational demands of the field, as it is intertwined with natural science disciplines, especially biology and chemistry. Accordingly, this paper advocates the formation of an interdisciplinary forensic studies program, including a discussion of need, curricular components, and overcoming potential obstacles.